Spin‐Noise‐Detected Two‐Dimensional Nuclear Magnetic Resonance at Triple Sensitivity. Issue 8 (20th February 2018) - Ginthör, Stephan J.; Chandra, Kousik; Bechmann, Matthias; Rodin, Victor V.; Müller, Norbert
Abstract: A major breakthrough in speed and sensitivity of 2 D spin‐noise‐detected NMR is achieved owing to a new acquisition and processing scheme called "double block usage" (DBU) that utilizes each recorded noise block in two independent cross‐correlations. The mixing, evolution, and acquisition periods are repeated head‐to‐tail without any recovery delays and well‐known building blocks of multidimensional NMR (constant‐time evolution and quadrature detection in the indirect dimension as well as pulsed field gradients) provide further enhancement and artifact suppression. Modified timing of the receiver electronics eliminates spurious random excitation. We achieve a threefold sensitivity increase over the original snHMQC (spin‐noise‐detected heteronuclear multiple quantum correlation) experiment (K. Chandra et al., J. Phys. Chem. Lett .2013, 4, 3853) and demonstrate the feasibility of spin‐noise‐detected long‐range correlation. Abstract : Triple sensitive spin‐noise NMR : A major breakthrough in speed and sensitivity of 2 D spin‐noise‐detected NMR is achieved owing to a new acquisition and processing scheme called "double block usage" (DBU) that utilizes each recorded noise block in two independent cross‐correlations.